Student Perception Relationships about Teacher and Pedagogy Learning Motivation with Education Learning Results Islamic Religion in SMP Negeri 12 Medan - Asnil Aida Ritonga; Eka Susanti; Juanda Juanda (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research aims to determine: (1) relationship between students' perceptions of teacher’s pedagogy and learning outcomes of Islamic  education,  (2) relationship between students’ learning motivation and students’ learning outcomes of Islamic education?, and  (3) relationship in line between students' perceptions of teacher’s pedagogy and learning motivation with the learning outcomes of Islamic education.  The type of this research is Quantitative Descriptive Correlational, with descriptive analysis. Data collection tools are using a likert scale questionnaire. The questionnaire was compiled based on the indicators of each variable and checked with the thesis supervisor, then the instrument test was carried out on the respondents and not the research sample.  The results showed that students' perception about teacher’s pedagogy and learning motivation had a relationship with the learning outcomes of Islamic education. In the research hypothesis test, the correlation (1) X1 and Y = r calculate was greater than the r table value (0.461 > 0.339) and the significance value was less than 0.05 (0.006 < 0.05). (2) the correlation of X2 with Y = r calculate is greater than the value of r table (0.409 > 0.339) and the significance value is less than 0.05 (0.016 < 0.05). (3) The correlation of X1 and X2 in line with Y = F calculate is greater than F table (5.089 > 3.30) and the significance value is less than 0.005 (0.012 < 0.05).